2017
DOI: 10.1111/bju.13903
|View full text |Cite
|
Sign up to set email alerts
|

Unification of favourable intermediate‐, unfavourable intermediate‐, and very high‐risk stratification criteria for prostate cancer

Abstract: Modifying the NCCN risk-stratification system to group FIR with low-risk patients and UIR with SHR patients, results in modestly improved prediction of outcomes, potentially allowing better personalisation of therapeutic recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
3
26
0
1
Order By: Relevance
“…Thus, these results are not necessarily applicable to all clinical practice environments or patient populations. However, our findings are consistent with what has been previously described for intermediate and high‐risk prostate cancer in other settings . The follow‐up for VHR patients was also significantly shorter than the follow‐up time for other patients in the SEARCH database.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, these results are not necessarily applicable to all clinical practice environments or patient populations. However, our findings are consistent with what has been previously described for intermediate and high‐risk prostate cancer in other settings . The follow‐up for VHR patients was also significantly shorter than the follow‐up time for other patients in the SEARCH database.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are remarkably consistent with a recent study of prostate cancer patients undergoing dose‐escalated radiation therapy (RT) with or without androgen deprivation therapy at a high‐volume academic institution . As in this study, VHR patients were found to have dramatically worse outcomes following RT in comparison to SHR patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They may now need to adapt their risk stratification based on ISUP grades. Indeed, the current National Comprehensive Cancer Network (NCCN) guidelines on prostate cancer distinguishes between favourable and unfavourable intermediate risk based, among others, on the distinction between ISUP grades 2 and 3 . Similarly, the Cancer of the Prostate Risk Assessment (CAPRA) score for biopsies and prostatectomy specimens distinguishes ISUP grades 2 and 3 .…”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
“…Indeed, the current National Comprehensive Cancer Network (NCCN) guidelines on prostate cancer distinguishes between favourable and unfavourable intermediate risk based, among others, on the distinction between ISUP grades 2 and 3. 47 Similarly, the Cancer of the Prostate Risk Assessment (CAPRA) score for biopsies and prostatectomy specimens distinguishes ISUP grades 2 and 3. 48 A potential disadvantage of the ISUP 2014 grading system might be the loss of the linkage with the underlying heterogeneity in carcinoma architecture.…”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%